2021
DOI: 10.1364/boe.440893
|View full text |Cite
|
Sign up to set email alerts
|

Temporal phase evolution OCT for measurement of tissue deformation in the human retina in-vivo

Abstract: We demonstrate the use of temporal phase evolution (TPE-) OCT methods to evaluate retinal tissue deformation in-vivo over time periods of several seconds. A custom built spectral domain (SD)-OCT system with an integrated retinal tracker, ensuring stable imaging with sub-speckle precision, was used for imaging. TPE-OCT measures and images phase differences between an initial reference B-scan and each of the subsequent B-scans of the evaluated temporal sequence. In order to demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…295 Phasesensitive OCT has also been extended into in vivo imaging of the human retina 296 and its associated motion. 297 However, despite great improvements in phase stability, there is a still often a need for either manual or automatic phase unwrapping to correct for phase errors with this emerging technique.…”
Section: Qpi In Tissues Andmentioning
confidence: 99%
See 1 more Smart Citation
“…295 Phasesensitive OCT has also been extended into in vivo imaging of the human retina 296 and its associated motion. 297 However, despite great improvements in phase stability, there is a still often a need for either manual or automatic phase unwrapping to correct for phase errors with this emerging technique.…”
Section: Qpi In Tissues Andmentioning
confidence: 99%
“…OCT and its’ high speed variants are low-coherence interferometry methods that leverage low temporal coherence to exclude scattered light outside a tissue slice of interest, coupled with backscattering of light, to image cross-sectional areas of tissues in situ . , An early approach added phase retrieval to OCT to enable QPI of human cheek cells (Figure a) and isolated chicken cardiomyocytes . Phase-sensitive OCT has also been extended into in vivo imaging of the human retina and its associated motion . However, despite great improvements in phase stability, there is a still often a need for either manual or automatic phase unwrapping to correct for phase errors with this emerging technique.…”
Section: Ongoing Developmentsmentioning
confidence: 99%
“…It was previously shown that the blood pulsation induces thickness changes that can be monitored with an accuracy that was estimated to 10 nm [6]. This method was used to measure the pulse wave velocity in retinal arteries [6], and recently implemented with scanning instruments [18]. The map of the local changes of retinal thickness between the end of diastole and the following systolic peak [time points indicated by the double headed arrow in Fig.…”
mentioning
confidence: 99%